2017
DOI: 10.1103/physrevc.95.024311
|View full text |Cite
|
Sign up to set email alerts
|

Probing resonances in the Dirac equation with quadrupole-deformed potentials with the complex momentum representation method

Abstract: Resonance plays critical roles in the formation of many physical phenomena, and many techniques have been developed for the exploration of resonance. In a recent letter [Phys. Rev. Lett. 117, 062502 (2016)], we proposed a new method for probing single-particle resonances by solving the Dirac equation in complex momentum representation for spherical nuclei. Here, we extend this method to deformed nuclei with theoretical formalism presented. We elaborate numerical details, and calculate the bound and resonant s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…In order to probe the single-particle resonances in the relativistic scheme, a method for solving the Dirac equation in the complex momentum space was developed recently. It has been found that this method is not only very effective for the narrow resonances, but also can be reliably applied to the broad resonances [15,16]. This is potentially crucial for understanding some exotic properties of halo nuclei.…”
Section: Covariant Density Functional Theorymentioning
confidence: 99%
See 3 more Smart Citations
“…In order to probe the single-particle resonances in the relativistic scheme, a method for solving the Dirac equation in the complex momentum space was developed recently. It has been found that this method is not only very effective for the narrow resonances, but also can be reliably applied to the broad resonances [15,16]. This is potentially crucial for understanding some exotic properties of halo nuclei.…”
Section: Covariant Density Functional Theorymentioning
confidence: 99%
“…In the right panel of Fig. 1, the SD excitations in 16 O are shown as an example. Note that the three components could not be distinguished experimentally until an experiment with the high-quality polarized proton beam performed in RCNP in 2011 [23].…”
Section: Nuclear Spin-isospin Excitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the conventional scattering phase shift method [54], several bound-state-like approaches [55,56], such as the analytical continuation in coupling constant [57,58,59,60,61,62], the real stabilization method [63,64,65] and the complex scaling method (CSM) [66,67,68,69], are often used to study single particle resonances in atomic nuclei. Several other methods, e.g., the Jost function method [70,71], the Green's function method [72,73], the Green's function + CSM [69,74], and solving Schrödinger or Dirac equations in the complex momentum representation [75,76], have also been implemented in nuclear models.…”
Section: The Weakly Bound Feature Of Exotic Nucleimentioning
confidence: 99%